Reviewing RAWP. Variations in admission rates: implications for equitable allocation of resources. Issue 6605 (24th October 1987) - Bevan, G; Ingram, R
Abstract : The review of the Resource Allocation Working Party (RAWP) formula by the National Health Service Management Board has considered the method used to account for cross boundary flows between health authorities. There is no consensus on how this should be done subregionally, as it raises the unresolved problem of the best method of estimating the size of catchment populations. Different methods produce different population sizes when the admission rates of individuals living in different districts vary. The National Health Service/Department of Health and Social Security acute services working group on performance indicators recently considered the assumptions made by different methods in terms of admission thresholds set by hospital clinicians. More complicated methods of assessing catchment areas seem to offer little advantage over the simplest method, but none of the methods answer the underlying questions of what truly determines admission rates and whether higher admission rates are better than lower ones. Empirical research into variations in admission rates and their relation to outcomes is important for determining the fair allocation of resources in future.